PENGARUH KARAKTERISTIK GENDER DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA KELAS X IPA 1 DI MAN 2 SEMARANG - Yalailati Kusnia (Universitas Muhammadiyah Semarang, 2017)
This study aims to describe the influence of gender characteristics and learning motivation of IPA 1st graders in Madrasah Aliyah Negeri 2 Semarang (MAN 2 Semarang). This research uses quantitative approach. The study population is all students of class X IPA 1 with the number of students as much as 40 people. Data were collected using questionnaire and documentation instruments. Data analysis used regression with dummy variable, simple regression, and multiple regression. The analysis was performed at a significance level of 5%. Research results show that: (1) There is no significant effect (p> 0,05) gender characteristics to student achievement. (2) There is a significant influence (p <0,05) learning motivation to student's mathematics learning achievement with contribution equal to 06,7%. (3) There is no significant effect (p> 0,05) between gender characteristic and learning motivation toward student's mathematics learning achievement with contribution equal to 08,2% Keywords: gender characteristics, learning motivation, learning achievement.